RANCANG BANGUN MESIN PRESS HIDROLIK PEMBUAT BENTUK DASAR HELM UKIR KHAS KOTAGEDE - Faradis, Muhammad Nabil Satria; Maksum, Hibran Sabila; Maulana, Irkham; Ratnasari, Rizka Islami; Daulay, Yulisyah Putri (Program Kreativitas Mahasiswa - Teknologi, 2014)
ASEAN Economic Community is a regional economic integration to envision ASEAN as a single market production base. AEC can increase Indonesiaâs export and introduce our culture, but it can ruin Indonesiaâs economy if UKM doesnât ready to face it. To help this problem, people need to enhance UKMâs prospects by increasing the usage of technology. This time, our partner is carved helmet UKM from Kotagede which represent creativity, art, and high quality aesthetic of Indonesia. Sadly, there is a problem happening to our partner. It is on the lenght of time and size of power needed to produce a plain helmet as the material for carved helmet since itâs still produced traditionally. Due to that problem, we offer a semi automatic process machine which called I-PAPS âINOVASI PROSES AUTOMASI PRODUKSI DENGAN PRESS SYSTEMâ As the Solution for Carved Helmet UKM from Indonesia Lead to ASEAN Economic Community 2015. This Press Machine will shape the plate of aluminium as the basic material to a plain helmet. This press machine works based on hidraulic system and accretion of calor. This hidraulic system works when the handle ismoved up and downto give more pressure so the shape of helmet can be formed to the basic material. With the same length of time with making a plain helmet manually, I-PAPS is able to increase productivity and produce seven plain helmet. Furthermore, we hope this machine can solve our partnerâs problem and help our partner to thrive, and also our long-term goal is to increase our partnerâs opportunity to compete in international market, especially to face AEC 2015.Keywords: Carved helmet from Indonesia, Press Machine, ASEAN Economic Community